2019
DOI: 10.1080/23802359.2019.1675551
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation and phylogenetic analysis of the complete mitochondrial genome of Ctenoplusia albostriata (Lepidoptera: Noctuidae: Plusiinae)

Abstract: Ctenoplusia albostriata is a pest of composite plants such as Calendula officinalis L. and Dahlia pinnata. In this study, we sequenced and analyzed the complete mitochondrial genome (mitogenome) of C. albostriata. This mitogenome was 15,284 bp long and encoded 13 protein-coding genes (PCGs), 22 transfer RNA genes (tRNAs), and 2 ribosomal RNA unit genes (rRNAs). Gene order was conserved and was found to be identical to most other previously sequenced Noctuidae. The whole mitogenome exhibited heavy AT nucleotide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
2
3
0
Order By: Relevance
“…However, the Hadeninae and Noctuinae are sister groups from the same superfamily (Fig 5). The phylogenetic tree confirmed that the previously characterized species C. albostriata [49], D. nadeja [50], and T. ni…”
Section: Phylogenetic Analysissupporting
confidence: 82%
See 2 more Smart Citations
“…However, the Hadeninae and Noctuinae are sister groups from the same superfamily (Fig 5). The phylogenetic tree confirmed that the previously characterized species C. albostriata [49], D. nadeja [50], and T. ni…”
Section: Phylogenetic Analysissupporting
confidence: 82%
“…Insect species like Ctenoplusia albostriata [ 49 ], Diachrysia nadeja [ 50 ], Trichoplusia ni [ 43 ], Laelia suffusa [ 51 ], Cerura menciana [ 22 ] and Eudocima salaminia [ 48 ] all have the same genes with little differences in size and location. The start codons for the cox1 gene in lepidopteran insects are not uniform [ 52 ], which has been widely debated and has long been a source of contention [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results shed light on the biological composition of this commercial medicinal material, in which both dietary species and introduced species due to hygiene problems were observed. In our study, Ctenoplusia albostriata (Bremer & Grey, 1853) 40 from Lepidoptera was found to be distributed in all samples from ten provinces in China. Coboldia fuscipes (Meigen, 1830) 41 , an oyster mushroom fly from Diptera, was also found to be distributed in all samples from ten provinces in China.…”
Section: Discussionsupporting
confidence: 47%
“… 2022 ), Ctenoplusia albostriata NC_053742.1 (Xue et al. 2019 ), Helicoverpa assulta NC_014668.1 (Seo et al. 2019 ), Helicoverpa armigera NC_014668.1 (Yin et al.…”
Section: Resultsmentioning
confidence: 99%